Karakteristik Kasus Severe Acute Respiratory Infection (SARI) di IndonesiaTahun 2008-2009 - -, Roselinda; AP, Krisna Nur (Central Basic Biomedical and Health Technology, 2013)
Severe Acute Respiratory Infection ( SARI ) pneumonia is an acute infection process oflung tissues with symptoms including fever, cough and difficulty breathing. Data showed that deaths in children < 5 years with pneumonia was approximately30 %.The objective of this article is to analyse the characteristics of the SARI cases in Indonesia in 2008-2009. The data analyzed were part of the data SARI laboratory based- surveillance in Indonesia in 2008-2009 . Specimens were collected from adult cases which include sputum, blood and throat swabs, and from children cases, which include blood and nasal swab. Diagnostic test were conducted bybacterial culture of blood and sputum, RT- PCR for influenza of nose and throat swabs and multiple beads array assay for a panel of bacteria and viruses. Clinical data and the results of laboratory tests are recorded and collected in sentinel hospitals and further analyzed in NIHRD byStata 09 program. SARI cases was more frequent in males 59 % and 0-5 years age group at 68 % . SARI comorbidities at mostisequal to 7% of tuberculosis. The final condition of SARI patients showed that 6 % died. Of the71caseswho diedmoreabundant inchildrenby69%compared toadultsand the largest age groupof 0-5 years are at 66%, followed by the age group> 60 years was12%with more deaths in children cases 7.4 % than in adult5 %. Those most vulnerable to the SARI is the children and the malegenderso that frequency of cases and deaths is higher in this group.Key words : Severe Acute Respiratory Infection, Surveillance, Indonesia.Â AbstrakSevere Acute Respiratory Infection (SARI) atau pneumonia merupakan proses infeksi akut yang terjadi pada jaringan paru dengan gejala, demam, batuk dan kesulitan bernafas. Kasus kematian pada anak < 5 tahun karena pneumonia berkisar 30%.Tujuan penulisan artikel ini adalah untuk melihat karakteristik kasus SARI pada Surveilans SARI di Indonesia tahun 2008-2009. Data yang dianalisis adalah bagian dari data Surveilans SARI di Indonesia tahun 2008-2009 yang berbasis laboratorium. Spesimen yang dikumpulkan adalah sputum, darah dan swab tenggorok diambil dari kasus dewasa, dan spesimen darah dan swab hidung dari kasus anak-anak. Dilakukan pemeriksaan kultur darah dan sputum, pemeriksaan RT-PCR pada swab hidung dan tenggorok serta multiple beads array assay untuk panel bakteri dan virus. Data klinis kasus dari status dan hasil pemeriksaan laboratorium dicatat, dikumpulkan di Rumah Sakit dan dikirim ke Pusat dengan memakai software stata 09 data dianalisis. Kasus SARI lebih banyak pada laki-laki sebesar 59% dan pada kelompok umur 0-5 tahun yaitu sebesar 68%. Penyakit penyerta pada SARI terbanyak adalah tuberkulosis sebesar 7%. Status akhir penderita SARI secara total meninggal sebesar 6%. Dari 71 kasus yang meninggal lebih banyak terdapat pada anak-anak sebesar 69% dibandingkan dewasa dan kelompok umur terbanyak adalah 0-5 tahun sebesar 66%, dikuti oleh kelompok umur >60 tahun sebesar 12%. Kelompok yang rentan terhadap terjadinya SARI adalah anak-anak dan jenis kelamin laki-laki sehinga frekuensinya kasus dan kematian lebih tinggi pada kelompok ini.Kata kunci: Severe Acute Respiratory Infection, Surveillans, Indonesia.